Education in Haor areas of Bangladesh: A mixed-methods study on academic performance, school attendance, and school intervention - Md. Ismail Hossain; Iftakhar Ahmad (PLoS ONE, 2026)
This study examines the factors affecting secondary education in the Tanguar Haor region of Bangladesh, employing a sequential explanatory design. Quantitative data were collected from 189 students across 10 randomly selected secondary schools using structured questionnaires, while qualitative insights were obtained through semi-structured interviews with 20 teachers and guardians, guided by an interview guideline. Descriptive and inferential analyses, including chi-square and logistic regression, were applied to quantitative data, and thematic analysis was used for qualitative data. Data analysis revealed that academic performance was strongly influenced by the number of teachers, bullying, peer support, class level, family income, teachers’ behavior, learning difficulty, marital status, and smartphone usage; school attendance was associated with parental education, school distance, and peer influence, while absenteeism was affected by similar academic, social, and household factors. Logistic regression indicated that students from higher-income families were more likely to achieve good academic outcomes (B = 2.129, p < .001, OR = 8.65, 95% CI [3.15, 23.72]), and peer support positively influenced performance (B = 1.359, p = .006, OR = 4.02, 95% CI [1.42, 10.63]). School attendance was positively predicted by parental education (B = 0.910, p = .009, OR = 2.48, 95% CI [1.25, 4.93]) and negatively influenced by greater school distance (B = –0.819, p = .013, OR = 0.44, 95% CI [0.23, 0.84]) and limited peer help (B = –0.832, p = .037, OR = 0.44, 95% CI [0.20, 0.95]). Chronic absenteeism increased with bullying (B = 1.361, p < .001, OR = 3.90, 95% CI [1.90, 7.99]) and punitive teacher behavior (B = 1.146, p = .009, OR = 3.15, 95% CI [1.33, 7.43]) and decreased with household work (B = –1.082, p = .022, OR = 0.34, 95% CI [0.14, 0.85]), higher family income (B = –1.350, p < .001, OR = 0.26, 95% CI [0.13, 0.53]), and peer influence (B = –0.920, p = .013, OR = 0.40, 95% CI [0.19, 0.82]). Qualitative findings corroborated these results, highlighting socio-economic and community-level barriers. Despite applying school intervention, educational challenges persist in Haor areas. Finally, the study recommends context-specific interventions to address challenges and enhance educational outcomes in this ecologically vulnerable region.